Baseline data on forest loss and associated uncertainty: advances in national forest monitoring - Johanne Pelletier; Scott J Goetz (Environmental Research Letters, 2015)
Countries participating in climate change mitigation via the United Nations Framework Convention on Climate Change reducing emissions from deforestation and forest degradation mechanism are required to establish national forest monitoring systems. The design of national forest monitoring system includes provision of transparent, consistent and accurate estimates of emissions and removals from forests, while also taking into account national circumstances and capabilities. One key component of these systems lies in satellite remote sensing approaches and techniques to determine baseline data on forest loss against which future rates of change can be evaluated. Advances in approaches meeting these criteria for measuring, reporting and verification purposes are therefore of tremendous interest. A robust example advancing such approaches, focused on Peru, is provided in the recent paper of Potapov et al (2014 Environ. Res. Lett. http://dx.doi.org/10.1088/1748-9326/9/12/124012 9 http://dx.doi.org/10.1088/1748-9326/9/12/124012 ).